Frontal polymerization-assisted 3D printing of short carbon fibers/dicyclopentadiene composites. (November 2021) - Zhang, Zimeng; Liu, Ruochen; Li, Wei; Liu, Yuchen; Pei, Zhijian; Qiu, Jingjing; Wang, Shiren
Abstract: Discontinuous carbon fibers (d-CFs) with different surface modifications (sizing, carboxyl-grafting, and norbornene-grafting) were separately dispersed in dicyclopentadiene (DCPD) resins, and the resultant d-CF/DCPD mixtures demonstrated shear-thinning characteristics. Subsequently, d-CF/DCPD mixtures were printed and further transformed into crosslinked polymers through self-propagating frontal polymerization. The norbornene groups grafted on the d-CF surfaces also reacted with the DCPD monomers during the fontal polymerization-synchronized printing, resulting in covalent connections between d-CFs and DCPD resins. The tensile strength of as-printed norbornene-grafting d-CFs/DCPD composites was around 43.3 MPa, which was 170% higher than that of as-printed neat DCPD resin and 15% higher than that of the sized d-CFs/DCPD composites. The toughness of as-printed norbornene-grafting d-CFs/DCPD composites was 14 MPa, 33.3% higher than that of the sized d-CF/DCPD composites. More importantly, the presence of norbornene-grafted d-CFs significantly strengthened the bonding strength of printed layers since d-CFs bridged two neighbored layers. The bonding strength of printed layers was enhanced by 255% with addition of 3 wt% norbornene-grafting d-CFs compared to the neat resin. This method provides a new way to improve the interlayer bonding in energy-efficient 3D printing thermosetting composites.